(3GdQYGjI aj GdSdhcs - (3CHh YHO Gddg GdMGQK Hf CSO GdeMGSHj, GdMGQK GdeMGSHj,J (B243 (3g` s
(3ChdgG (B:s
(3GdMeO ddg bHd cd ebGd hCeGe cd QZHI hSDGd hcd CeQ ege Pi HGd s
(3BNQgG (B:s
(3hdG bhI EdG HGddg aefg GdYUeI hYdjg GdJcdGf fSCdg JeGe GdfYeI YdjfG hQMeJg hUdi Gddg Ydi eMeO fHjgq s
(3Ydi dhMI GdYfhGf JedcGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B153 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B517s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B908s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdJUha hGdBOGH GdTQYjIs